Type-B response regulator RRB12 regulates nodule formation in Lotus japonicus - Jingjing Cao; Yu Zhou; Tao Tian; Jie Ji; Yan Deng; Yuhao Guan; Yongmei Qi; Longxiang Wang; Longlong Wang; Yibo Huang; Qiuling Fan; Deqiang Duanmu (BMC Biology)
Abstract Background The mutualistic beneficial relationship between legume plants and rhizobia enables the growth of plants in nitrogen-limiting conditions. Rhizobia infect legumes through root hairs and trigger nodule organogenesis in the cortex. The plant hormone cytokinin plays a pivotal role in regulating both rhizobial infection and the initiation of nodule development. However, the mechanism used by the cytokinin output module to control symbiosis remains poorly documented. Results In this study, we identified a cytokinin signaling output component encoded by the Type-B RESPONSE REGULATOR (RRB) gene, LjRRB12, which is expressed in Lotus japonicus nodule primordia and young nodules. Disruption of LjRRB12 leads to a reduction in nodulation and to an increase in the number of infection threads. Overexpression of LjRRB12D76E, an active form of the LjRRB12 protein, induces nodule-like structures in wild type and hit1 (hyperinfected 1/lotus histidine kinase 1) mutants but not in nin2 (nodule inception 2) mutants. Additionally, we utilized nCUT&Tag and EMSA to demonstrate that LjRRB12 can bind a CE (cytokinin response element) from the LjNIN promoter. Conclusions Our results provide a deeper understanding of nodule organogenesis by establishing a link between the cytokinin signal and the transcriptional regulation of LjNIN.